PENDIDIKAN AGAMA KRISTEN SEBAGAI SARANA TRANSFORMASI SOSIAL DI MASYARAKAT MULTIKULTURAL - Fifianti Rudy; Misel Ratte, Lusiana, Fani Ando’, Irmawansi Rorrong (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2025)
Christian Religious Education (PAK) plays a strategic role in shaping the character, morals, and leadership of students, while also serving as a vehicle for social transformation in a multicultural society. This article aims to analyze how PAK can instill Christian values, develop leadership based on love and justice, and foster social solidarity relevant to cultural and religious diversity. The research method used is a literature review with a descriptive qualitative approach, examining various scientific literature, journals, and relevant books discussing the role of PAK in character education, multiculturalism, and social transformation. The results indicate that the integration of multicultural values into the curriculum, the role of teachers as facilitators, and the implementation of collaborative learning activities and social services are key to PAK's success in shaping a young generation with character, tolerance, and social responsibility. This article provides important implications for the development of PAK curricula and learning strategies that support character and leadership formation in the context of a multicultural society